HIV testing and linkage to care-A case of a mobile diagnostic and counseling service in Mbeya, Tanzania; A quantitative study. - Amani Kway; Issa Sabi; Willyhelmina Olomi; Ruby Doryn Mcharo; Erica Sanga; Wiston William; Ombeni Chimbe; Nyanda Elias Ntinginya; Lucas Maganga (Public Library of Science (PLoS), 2022)
HIV-care programmes are faced with significant challenges in getting newly diagnosed People Living with Human Immunodeficiency Virus (PLHIV) linked to care despite massive investment in HIV prevention, treatment and care. This study assessed the performance of mobile HIV Testing and Counseling service (mHTC) in provision of HIV-testing and linkage to care of newly diagnosed PLHIV from Key and Vulnerable Populations (KVPs). A retrospective review of the records of 25,248 clients was extracted from the mHTC database from October-2016 to September-2018. Of 25,248 clients, 51.71% were in 25-45 years age group, 55.4% were males, 60.5% were married and 62.1% had primary level of education. The median age of clients was 31 (IQR: 23-42) years. Out of the clients tested, 800 (3.17%) were diagnosed HIV-positive. Positivity was high among females 450 (4%), age group 25-45 years 538 (4.12%), divorced 202 (7.41%) and clients with primary level of education 504 (3.21%). An association between HIV status and sex, age group, relationship status and level of education was observed (P<0001). Out of the 800 HIV-positive clients, 418 (52.30%) were successfully linked to care. Among the positive clients, 5/6 (83.33%) children below 15 years old, 238/450 (52.89%) females and 39/64 (60.94%) widows were successfully linked to care. In the multivariable log binomial regression model age of the clients was associated with successful linkage to care. The mHTC was able to reach KVP clients; overall linkage for both sexes was 52.30% below the recommended UNAIDS 90-90-90 target. Raising the need to address the challenges associated with linkage and specific care for KVPs as a subset of the general population. The mHTC has shown that it is feasible to improve the reach of KVP clients; however, further research is required to examine the quality of this service at the community level.